Use Of Neurological Rating Scales In The Study Of Pain Symptoms In Salpingoophoritis Complicated With Chronic Pelvic Pain Syndrome. (Eurasian Scientific Herald, 2025)
We used neurological rating scales to teach patients to self-report pain symptoms in salpingo-oophoritis complicated by chronic pelvic pain syndrome. The results obtained were recommended for the study of clinical symptoms of salpingo-oophoritis complicated by chronic pelvic pain syndrome.